First report of phthalate acid esters (plasticizers) in blubber of southern right whales (Eubalaena australis) from Península Valdés, Argentina - Luciana Gallo; Melina Paola Michlig; Maria Rosa Repetti; Agustina Donini; Adrian E. Rodriguez; Mariano Sironi; Marcela M. Uhart (Polar Biology, 2026)
Phthalate acid esters (PAEs) are widely used plastic additives that have become ubiquitous contaminants in marine environments. Filter-feeding baleen whales may be exposed to these pollutants through water, prey or ingested plastic debris. While macroplastics have been reported in the gut of a southern right whale (SRW, Eubalaena australis ), exposure to PAEs has not been assessed. Here, we quantified three lipophilic PAEs, dimethyl phthalate (DMP), dibutyl phthalate (DBP), and di-2-ethylhexyl phthalate (DEHP), in the blubber of 13 SRWs (three calves, three juveniles and seven adults) stranded in 2021 at Península Valdés, Argentina. More than 90% of samples contained detectable PAE levels, and 46.2% were above quantification limits. DEHP and DBP were the most prevalent compounds (61.5% and 30.8%, respectively), although the biological significance of the detected concentrations remains uncertain. This is the first report of PAEs in SRW blubber and suggests potential mother-calf transfer, highlighting exposure of Southern Hemisphere mysticetes to plastic-derived chemicals.

Germination and toasting shape composition and sensory quality of black creole maize flours for atole - Margarita I. Hernández-Urbiola; Mariana Ponce-Mendoza; Ezequiel Hernández-Becerra; Marcela Gaytán-Martínez; Edgar A. Esquivel-Fajardo; Fernanda Martinez-Hernandez; Oscar Y. Barrón-García; Mario E. Rodriguez-Garcia (Food and Humanity, 2026)

High frequency of plastic-derived contaminants (phthalate acid esters) in the preen gland of dead procellariiform seabirds from the Patagonian Sea - Luciana Gallo; María Rosa Repetti; Melina Paola Michlig; Leandro L. Tamini; Leandro N. Chavez; Ruben F. Dellacasa; C. Karina Alvarez; Sergio A. Rodriguez Heredia; Ralph Eric Thijl Vanstreels; Patricia Pereira Serafini; Marcela M. Uhart (Marine Pollution Bulletin, 2026)

Impact of high-amylose starch addition on the resistant starch content and the physicochemical properties of maize (Zea mays L.) cookies - Ludy M. Martinez-Rubio; Ivan Luzardo-Ocampo; Oscar Y. Barrón-García; Mario E. Rodriguez-García; Guadalupe Loarca-Piña; Marcela Gaytán-Martínez (Food Chemistry, 2026)

Scorpion venom gland transcriptomics: A systematic review - Jennifer Alexandra Solano-Godoy; Melissa Betancourt-Osorio; Marcela Orjuela-Rodriguez; Jimmy Alexander Guerrero-Vargas; Juan Carlos Sepulveda-Arias (Toxicon, 2025)

Evaluation of the efficacy of polymeric antigen BLSOmp31 formulated in a new cage-like particle adjuvant (ISPA YOLK) administered by parenteral or mucosal routes against Brucella ovis in rams - María Celeste Moran; Agostina Tammone Santos; Paula Dominguez; Lucila Moriones; María Victoria Nieto Farias; Laura Maté; Juan Agustín García; Tobias Kuhn; Fernando Alberto Paolicchi; María Andrea Fiorentino; Marcelo Gastón Rodriguez; Jorge Pablo García; et al. (Veterinary Immunology and Immunopathology, 2025)

Development of a biotechnological process for the production of recombinant canine interferon-alpha using the baculovirus-insect cell and larvae system - Maria S. Rodriguez; Ignacio Smith; Marcela S. Villaverde; Joaquin M. Birenbaum; Joaquin Poodts; Federico J. Wolman; Alexandra M. Targovnik; Maria V. Miranda (Biotechnology Letters, 2025)

Influence of nixtamalization time and solid-state fermentation on masa starch: Morphology, structure, and physicochemical properties - Cecilia Martinez-Ortiz; Oscar Y. Barron-Garcia; Mario E. Rodriguez-Garcia; Eduardo Morales-Sánchez; Mar Villamiel; Marcela Gaytán-Martínez (Innovative Food Science & Emerging Technologies, 2025)

Microplastics in the digestive tract of an endangered cetacean of the Southwest Atlantic Ocean: The franciscana dolphin - Antonella D. Padula; Ana C. Ronda; Lucas S. Rodríguez Pirani; A. Lorena Picone; Rosana M. Romano; Gisela V. Giardino; Juan Pablo Seco Pon; Rodrigo Machado; Marcela Gerpe; Diego Rodriguez; Pablo Denuncio (Marine Pollution Bulletin, 2025)

High frequency of plastic ingestion in procellariiform seabirds (albatrosses, petrels and shearwaters) in the Southwest Atlantic Ocean - Luciana Gallo; Patricia P. Serafini; Ralph E.T. Vanstreels; Leandro L. Tamini; Cristiane K.M. Kolesnikovas; Alice Pereira; Tatiana Neves; Gabriel D. Nascimento; Lucas S. Rodriguez Pirani; A. Lorena Picone; Rosana M. Romano; C. Karina Alvarez; et al. (Marine Pollution Bulletin, 2024)

Summarized cereal grain characteristics affecting digestive behavior and nutrient utilization on a quantitative basis: Comparison among oat, hull barley, and hulless barley grain - Marcela R. Tosta; Ganqi Deng; Luciana L. Prates; Ling Yang; Jiangfeng He; Maria E. Rodriguez Espinosa; Hongyu Deng; Weixian Zhang; Xiaogang Yan; Xin Feng; Huihua Zhang; Peiqiang Yu (Journal of Cereal Science, 2024)

Physicochemical changes in Amaranthus spp grains, flour, isolated starch, and nanocrystals during germination and malting - Elsa Gutiérrez-Cortez; Ezequiel Hernandez-Becerra; Luis Fernando Zubieta-Otero; Marcela Gaytán-Martínez; Oscar Yael Barrón-García; Mario Enrique Rodriguez-Garcia (Food Chemistry, 2024)

Water temperature and microenvironmental factors predict the presence and detection of the snail host of Fasciola hepatica in Andean Patagonia - Ana C. Rodriguez Quinteros; Paula Soler; Marcela Larroza; Juan M. Morales; Juan M. Gurevitz (Veterinary Parasitology, 2024)

Physicochemical changes in starch during the conversion of corn to tortilla in the traditional nixtamalization process associated with RS2 - Isela Rojas-Molina; María G. Nieves-Hernandez; Elsa Gutierrez-Cortez; Oscar Y. Barrón-García; Marcela Gaytán-Martínez; M.E. Rodriguez-Garcia (Food Chemistry, 2024)

Glandular trichomes as a source of antifungal metabolites in a karyologically characterized population of Argyrochosma flava: Morphology and histochemistry - Ana M. Rodriguez; Marcos G. Derita; Aldo R. Andrada; Valeria de los A. Páez; Mónica Ponce; Olga G. Martínez; Diego A. Neira; Marcela A. Hernández (Flora, 2024)

Study of morphological, structural, pasting, thermal, and vibrational changes in maize and isolated maize starch during germination - María G. Nieves-Hernández; Brenda L. Correa-Piña; Edgar A. Esquivel-Fajardo; Oscar Y. Barrón-García; Marcela Gaytán-Martínez; Mario E. Rodriguez-Garcia (Journal of Cereal Science, 2023)

Multi-level responses of oysters Crassostrea virginica for assessing organochlorine pesticides in a Ramsar coastal lagoon in southern Mexico - Mariana V. Capparelli; Guadalupe Ponce-Vélez; Ricardo Dzul-Caamal; Erick M. Rodriguez-Cab; Marcela Cabrera; Oscar Lucas-Solis; Gabriel M. Moulatlet (Chemosphere, 2023)

Measurement of airborne nicotine, as a marker of secondhand smoke exposure, in homes with residents who smoke in 9 European countries - Elisabet Henderson; Luis A. Rodriguez Guerrero; Xavier Continente; Esteve Fernández; Olena Tigova; Nuria Cortés-Francisco; Sean Semple; Ruaraidh Dobson; Anna Tzortzi; Vergina K. Vyzikidou; Giuseppe Gorini; Gergana Geshanova; et al. (Environmental Research, 2023)

Correction: Amphibian phylogenetic diversity in the face of future climate change: not so good news for the Chilean biodiversity hotspot - Leonardo J. Rodriguez; Olga A. Barbosa; Claudio Azat; Mario Alvarado-Rybak; Claudio Correa; Marco A. Méndez; Felipe N. Moreno-Gómez; Felipe E. Rabanal; Marcela A. Vidal; Nelson A. Velásquez; Leonardo D. Bacigalupe (Biodiversity and Conservation, 2022)

Amphibian phylogenetic diversity in the face of future climate change: not so good news for the chilean biodiversity hotspot - Leonardo J. Rodriguez; Olga A. Barbosa; Claudio Azat; Mario Alvarado-Rybak; Claudio Correa; Marco A. Méndez; Felipe N. Moreno-Gómez; Felipe E. Rabanal; Marcela A. Vidal; Nelson A. Velásquez; Leonardo D. Bacigalupe (Biodiversity and Conservation, 2022)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Autophagy Stimulation Decreases Dopaminergic Neuronal Death Mediated by Oxidative Stress - Marcela J. Ramirez-Moreno; Ana P. Duarte-Jurado; Yareth Gopar-Cuevas; Alfredo Gonzalez-Alcocer; Maria J. Loera-Arias; Odila Saucedo-Cardenas; Roberto Montes de Oca-Luna; Humberto Rodriguez-Rocha; Aracely Garcia-Garcia (Molecular Neurobiology, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Comparison of two protocols for field immobilization of white-eared opossums (Didelphis albiventris) - Samanta Waxman; Marcela Orozco; Hernán Argibay; Casilda Rodriguez; Pablo Otero (European Journal of Wildlife Research, 2018)

Identification of a Novel Moth Sex Pheromone Component from Chilecomadia valdiviana - Heidy Herrera; Wilson Barros-Parada; M. Fernanda Flores; Wittko Francke; Eduardo Fuentes-Contreras; Marcela Rodriguez; Francisca Santis; Paulo H. G. Zarbin; Jan Bergmann (Journal of Chemical Ecology, 2016)

Late Holocene climate and environment of the SE Pampa grasslands, Argentina, inferred from biological indicators in shallow, freshwater Lake Nahuel Rucá - Silvina Stutz; C. Marcela Borel; Sonia L. Fontana; Laura del Puerto; Hugo Inda; Felipe García-Rodriguez; Marcela S. Tonello (Journal of Paleolimnology, 2010)

Utilization of Fe3+-acinetoferrin analogs as an iron source by Mycobacterium tuberculosis - G. Marcela Rodriguez; Richard Gardner; Navneet Kaur; Otto Phanstiel (BioMetals, 2008)